Hepatic mRNA expression of innate and adaptive immune genes in beef steers with divergent residual body weight gain - Ologunagba, Deborah; Idowu, Modoluwamu; Taiwo, Godstime; Sidney, Taylor; Treon, Emily; Eichie, Francisca; Bebe, Frederick; Ogunade, Ibukun M. (Frontiers in Animal Science, 2024)
We evaluated the hepatic mRNA expression of genes involved in innate and adaptive immunity in crossbred beef steers with positive or negative residual body weight gain (RADG). Positive-RADG beef steers (n = 8; RADG = 0.73 kg/d) and negative-RADG beef steers (n = 8; RADG = -0.69 kg/d) were identified from a group of 108 growing crossbred after a 56-d performance testing period. Liver tissue samples were collected for RNA extraction and cDNA synthesis. The mRNA expression of 84 genes involved in immunity was analyzed using pathway-focused PCR-based arrays. The mRNA expression of genes with false discovery rate-adjusted P-values ≤ 0.05 and absolute fold change (FC) ≥ 1.2 were determined to be differentially expressed. Four genes (IL-2, MYD88, CD-80, NFkB-1) were differentially expressed and were all upregulated in positive-RADG beef steers. IL-2 is a cytokine that plays a critical role in the immune response by activating and proliferating T-cells. MYD88 is an adaptor protein that is essential for signaling by toll-like receptors. CD80 is a protein that is expressed on the surface of antigen-presenting cells and plays a critical role in the initiation of an immune response. The activation of NF-κB leads to the production of cytokines and chemokines that help to recruit immune cells to the site of infection. The upregulation of the aforementioned genes in positive-RADG beef steers suggests that they had a better ability than negative-RADG beef steers to quickly recognize pathogens and initiate appropriate responses to effectively fight off infections without causing inflammatory reactions.